Grass carp reovirus VP56 represses interferon production by degrading phosphorylated IRF7. Issue 99 (April 2020) - Zhang, Can; Lu, Long-Feng; Li, Zhuo-Cong; Zhou, Xiao-Yu; Zhou, Yu; Chen, Dan-Dan; Li, Shun; Zhang, Yong-An
Abstract: Grass carp reovirus (GCRV) is an efficient pathogen causing high mortality in grass carp, meanwhile, fish interferon (IFN) is a powerful cytokine enabling host cells to establish an antiviral state; therefore, the strategies used by GCRV to escape the cellular IFN response need to be investigated. Here, we report that GCRV VP56 inhibits host IFN production by degrading the transcription factor IFN regulatory factor 7 (IRF7). First, overexpression of VP56 inhibited the IFN production induced by the polyinosinic-polycytidylic acid (poly I:C) and mitochondrial antiviral signaling protein (MAVS), while the capacity of IRF7 on IFN induction was unaffected. Second, VP56 interacted with RLRs but did not affect the stabilization of the proteins in the normal state, while the phosphorylated IRF7 activated by TBK1 was degraded by VP56 through K48-linked ubiquitination. Finally, overexpression of VP56 remarkably reduced the host cellular ifn transcription and facilitated viral proliferation. Taken together, our results demonstrate that GCRV VP56 suppresses the host IFN response by targeting phosphorylated IRF7 for ubiquitination and degradation. Highlights: VP56 inhibits IFN activation induced by MAVS. VP56 induces the K48-linked ubiquitination and degradation of phosphorylated IRF7. VP56 blocks the cellular IFN response and facilitates viral replication.